Coping styles and achievement motivation in elite wrestlers - Rutkowska, K.; Gierczuk, D. (Archives of Budo Science of Martial Arts and Extreme Sports, 2018)
Background &Study Aim: Coping styles and achievement motivation are factors that, according to some authors, determine athletes` psychosocial sports and life-related effectiveness. The findings of the present study constitute an element of more extensive research plan. The study sought to knowledge about coping styles and dimensions of achievement motivation in elite wrestlers.